The success of community-based management in improving maintenance hemodialysis outcomes: a pilot study - Shi, Hui; Fan, Lei (Frontiers in Nutrition, 2025)
Background and aimPatients on maintenance hemodialysis (MHD) experience various complications, including malnutrition, reduced physical function, and psychological problems. Single-discipline medical approaches prove inadequate in addressing these complex situations. The multidisciplinary management model adopted by the nutritional support team has demonstrated effectiveness in managing such challenges. However, patient compliance remains suboptimal due to limited understanding of treatment regimens, fatigue from prolonged therapy, and insufficient psychological support. Consequently, establishing a patient-centered, transparent, and interactive communication platform is essential to improving treatment adherence through enhanced patient support.MethodsThis prospective randomized controlled trial assigned patients to either an experimental group receiving community-based management or a control group receiving traditional management. Health status was evaluated through laboratory parameters, body composition analysis, anthropometric measurements, and standardized scale assessments.ResultsA total of 28 patients with MHD were enrolled. Four patients died from primary disease (1 in the experimental group and 3 in the control group), leaving 24 who completed the trial. Statistical analysis was conducted on a dataset of 24 patients, including 13 in the experimental group and 11 in the control group. Seven outcomes demonstrated statistically significant differences. In terms of laboratory parameters, the experimental group achieved superior outcomes in serum albumin (12 patients, 92.3% versus 3 patients, 27.3%; p = 0.002), hemoglobin (11 patients, 84.6% versus 4 patients, 36.4%; p = 0.033), and blood phosphorus levels (10 patients, 76.9% versus 2 patients, 18.2%; p = 0.012), compared to control group. Body composition analysis indicated greater improvement in muscle mass (9 patients, 69.2% versus 3 patients, 27.3%; p = 0.038) and more favorable visceral fat distribution (11 patients, 84.6% versus 3 patients, 27.3%; p = 0.011) in the experimental group. Additionally, the experimental group scored higher on the Short Physical Performance Battery (SPPB; 10 patients, 76.9% versus 3 patients, 27.3%; p = 0.038) and exhibited better treatment compliance (10 patients, 76.9% versus 2 patients, 18.2%; p = 0.012). Notably, compliance mediated the effect of community-based management on SPPB scores (Proportion Mediated = 76.2%; p = 0.038).ConclusionCommunity-based management by the nutrition support team substantially improves patient compliance and enhances clinical outcomes.Clinical trial registrationchictr.org.cn, identifier ChiCTR2500104523.